Law Enforcement Officers' Perceptions of Child Offenders in Digital Crimes within the Juvenile Justice System - Wilsa Wilsa; Istiana Heriani; Vegitya Ramadhani Putri (JURNAL AKTA, 2026)
The rise of digital crimes involving minors has become a significant challenge for law enforcement officers within the juvenile justice system. The complexity and rapid evolution of digital offenses, such as hacking and online fraud, have made it difficult for law enforcement to address these crimes effectively, especially with minors involved. This study aims to analyze law enforcement officers' perceptions of child offenders in digital crime cases and explore the challenges they face in handling such offenses. Using a qualitative library research approach, data were collected from books, academic journals, legal documents, and previous research on digital crimes, juvenile delinquency, and law enforcement practices. The findings indicate that law enforcement officers often feel inadequately trained and underprepared to handle digital crimes committed by minors, leading to inconsistent responses. While officers generally prefer rehabilitation over punishment for minors, the lack of specialized legal frameworks and technical knowledge complicates the handling of these cases. The study concludes that specialized training, updated legal frameworks, and an integrated approach between law enforcement, educational institutions, and social services are necessary to effectively address digital crimes involving minors.